A comparison of image quality of cerium oxide nanoparticles and iodine contrast agents in computed tomography scan - Nasrullah, Faiz; Nurhasanah, Iis; Triadyaksa, Pandji; Rukmono, Dito Andi (Jurnal Pijar Mipa, 2023)
Computed tomography (CT) scan, with iodine-based contrast, produces good image quality by improving the visualisation of relatively low-contrast internal body structures. However, the impact of using iodinated difference should be considered in patients susceptible to contrast allergy and renal impairment. Therefore, alternative contrast materials, such as cerium oxide nanoparticles (CeO2 NPs), must be used, with biocompatible properties and strong X-ray attenuation capabilities. This study compared the CT scan image quality of CeO2 NPs and iodinated contrast agents. This experimental study started by preparing a suspension of CeO2 NPs and iodine in aquabidest at a concentration of 500 ppm. The suspension was scanned using a CT scan with a helical scanning method. The exposure coefficient parameters were set for the tube voltage of 80 kV, Field of View of 28 cm, slice thickness of 5 mm, and tube current time of 150 mAs, 200 mAs, and 250 mAs. Then, CT images in DICOM data format were processed using MicroDICOM Viewer software. The quality of the CT scan images was analysed based on the CT number value, noise level, and contrast resolution. The images of CeO2 nanoparticles have higher CT values, lower noise levels, and better contrast resolution than those of iodine contrast agents. The results show that the CT image results of CeO2 NPs have better quality than those of iodine-containing contrast agents.